Impacto del ejercicio continuo y intervalico sobre la respuesta autonómica y presora en 24 horas - Casonatto, Juliano; Domingues, Veridiana; Christofaro, Diego Giulliano Destro [UNESP] (FapUNIFESP (SciELO), 2016)
Introduction: Continuous aerobic exercises are the most related to post-exercise hypotension. However, there is little information on the impact of interval exercises on blood pressure response in 24 hours. Objective: To compare subacute and acute pressure responses of a continuous and interval aerobic exercise session and identify possible modulations in autonomic activity indicators in normotensive adults. Methods: Twenty-five healthy normotensive adults underwent three experimental sessions: control (30 minutes at rest), continuous exercise (30 min, 60-70% HRres) and interval exercise (six 5-minute sessions with 2 min intervals - 60-70% HRres), and their cardiovascular parameters were monitored for 24 hours after sessions. To compare the data, we used ANOVA for repeated measures, followed by their hypotheses. Results: Significant reduction was identified in the subacute follow-up (P < 0.05) in systolic blood pressure only after continuous exercise session, compared to the rest session(115±2 mmHg vs. 112±2 mmHg) and control (119±2 mmHg vs. 112±2 mmHg) sessions. No ambulatory blood pressure reduction was found in any of the experimental sessions. The parasympathetic autonomic indicators (RMSSD and pNN50) remained reduced after 30 minutes in both exercise sessions. Conclusion: A single continuous aerobic exercise session causes subacute reduction in blood pressure in normotensive adults. A single session of continuous and interval aerobic exercise does not promote reduction of ambulatory blood pressure in interim periods of sleep and wakefulness.
Impacto do exercício contínuo e intervalado na resposta autonômica e pressórica em 24 horas
Impact of continuous and interval exercise on the autonomic and pressoric response in 24 hours
Keywords: Ambulatory; Arterial pressure; Monitoring; Post-exercise hypotension